The effect of the physical exercise intervention on negative emotions in children and adolescents with neurodevelopmental disorders: a systematic review and meta-analysis - Wang, Anning; Peng, Yingying; Cui, Zhibo; Zhang, Qiubo; Wang, Tong (Frontiers in Psychiatry, 2025)
ObjectiveThis systematic review and meta-analysis aimed to synthesize existing evidence on the association between physical exercise (PE) interventions and negative emotions (NEs), including anxiety and depressive symptoms, among adolescents and children with neurodevelopmental disorders (NDDs), while carefully considering sample size limitations and evidence heterogeneity.MethodsRelevant studies were obtained from PubMed, EBSCO, Cochrane, Web of Science, Embase, and PsyINFO databases up to 27 June, 2025. Key search terms included NEs, PE, adolescents and children, and NDDs. Meta-analysis was performed utilizing Review Manager 5.3, applying a random-effects model to estimate the standardized mean difference (SMD) along with 95% confidence intervals (CI). Subgroup analyses were conducted based on the type of negative emotion, intervention modality, duration, timing, and frequency.ResultsPE interventions were associated with a statistically significant overall reduction in NEs in adolescents and children with NDDs (SMD = -0.60, 95% CI: -1.02 to -0.18, p < 0.01, Z = 2.80, I² = 79%). The effect was most evident for anxiety (SMD = -0.56, 95% CI: -1.11 to -0.00, p = 0.05, I² = 83%), suggesting a potential reduction in anxiety symptoms that approaches statistical significance. However, the findings for depressive symptoms were inconclusive (SMD = -0.82, 95% CI: -2.00 to -0.36, p = 0.17, I² = 87%), likely due to heterogeneity in interventions, small sample sizes, and variability in measurement tools. Subgroup analysis suggested that engaging in mixed forms of PE for a minimum of 60 minutes per session, once weekly, over a 12-week period, was especially effective in improving emotional well-being in this population.ConclusionThis study highlights the potential of PE interventions to alleviate negative emotions—especially anxiety—among adolescents and children with NDDs, but emphasizes that evidence for depressive symptoms remains inconclusive. The findings should be interpreted with caution due to limited study numbers, predominance of ADHD-focused samples, heterogeneity across studies, and reliance on subjective assessment tools. Future high-quality, adequately powered randomized controlled trials are warranted to confirm these effects and clarify optimal intervention parameters.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, identifier CRD420251081387